Psychometric analysis of underachievement tool for gifted students - Marilena Z. Leana-Taşcılar (Cogent Education, 2024)
This study aimed to develop a comprehensive tool to assess underachievement in gifted students, incorporating input from parents, teachers, and students themselves. A total of 285 participants, including 95 gifted students, their parents, and teachers, were involved in the study. The results have revealed a four-factor structure for the Gifted Underachievement Tool, with strong evidence supporting its validity and reliability. The study discusses the limitations of using this tool for the identification of underachievement in gifted students and draws significant conclusions from the findings.